IMPROVING LITERACY AND CREATIVITY CULTURE OF STUDENTS THROUGH THE UTILIZATION OF THE WALL OF EXPRESSION AT PAMULANG TENGAHSTATE ELEMENTARY SCHOOL - Alexius Easton Ance; Risfa Andria Nuraini; Nurul Fadhilah Sari; Nia Anjani; Mutiaraziom Susanti; Laili Dwi Utami; I Made Leo Mardaragawan; Feni Auliansah; Anita Kurniasih; Shavira Ramadhani (LPPM STAI Muhammadiyah Probolinggo, 2025)
This community service project aims to enhance students’ literacy and creativity through the implementation of the “Expression Wall” at SDN Pamulang Tengah, South Tangerang. The project was designed to provide a space where students can express their ideas, artistic works, and reflections freely, thus fostering an engaging learning environment. The method used was participatory action with four stages: preparation, implementation, monitoring, and evaluation. During the implementation phase, students and teachers participated in socialization and hands-on activities to introduce and utilize the Expression Wall. The results show that the Expression Wall effectively increased students’ interest in reading, writing, and creative expression. Students became more active in producing and appreciating creative works displayed on the wall, while teachers acted as facilitators to support literacy-based learning. The monitoring phase confirmed a growing sense of collaboration, independence, and responsibility among students. Overall, the project successfully promoted a culture of literacy and creativity, proving that a simple yet innovative medium can significantly improve students’ engagement and school atmosphere.